STRATEGI PEMASARAN DALAM MEMPERTAHANKAN USAHA MIKRO KECIL MENENGAH (UMKM) KULINER (STUDI DI DESA BABUSSALAM KECAMATAN PUJUD KABUPATEN ROKAN HILIR) - roma dani; Mariatul Fitri (Finest : Jurnal Riset dan Pengembangan Ekonomi Islam, 2023)
Technological developments and increasingly high business competition make Micro, Small and Medium Enterprises (MSMEs) actors must have a marketing strategy in maintaining good MSMEs to remain competitive with their competitors. This research was conducted to find out the marketing strategy carried out by SMEs in maintaining their business in the face of competition. The research method in this study uses a descriptive qualitative approach through structured interviews with the perpetrators or top level management of MSMEs. The results of the study show that these culinary MSMEs provide added value and differentiation to the products and services provided, while in terms of price, they apply competitive and competitive prices. The application of technology is also very influential in increasing income as a means of promotion for their business as well as social media to establish good relations and communicate with consumers.